1999
DOI: 10.1300/j145v03n01_05
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in Adolescent and Older-Child Adoptions

Abstract: This column reviews and comments on studies of the outcome of older-child and adolescent adoption. The research demonstrates that children adopted at older ages are more likely to exhibit higher levels of some problem behaviors than children adopted at younger ages. Gender, age and the placement of sibling groups are among the variables that seem to influence outcome. [Article copies available for a fee from The Haworth Document Delivery Service: 1-800-342-9678. E-mail address: getinfo@ haworthpressinc.com Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Multiple changes in foster care placement over a 12-month period for foster youth relate to negative child externalizing and internalizing behaviors, including anxiety, aggression, and hyperactivity (Newton, Litrownik, & Landsverk, 2000). Finally, as children get older, their likelihood of being adopted decreases, and they may have more difficulty adjusting to adoptive placements (Haugaard, Wojslawowicz, & Palmer, 1999).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple changes in foster care placement over a 12-month period for foster youth relate to negative child externalizing and internalizing behaviors, including anxiety, aggression, and hyperactivity (Newton, Litrownik, & Landsverk, 2000). Finally, as children get older, their likelihood of being adopted decreases, and they may have more difficulty adjusting to adoptive placements (Haugaard, Wojslawowicz, & Palmer, 1999).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Little research has rigorously examined risk factors associated with discontinuity for former foster youth. However, some studies suggest that children who exhibit difficult behaviors, older children, and child victims of sexual abuse may be at increased risk for post-adoption or guardianship placement instability, and that other child factors may impact discontinuity as well, such as gender, placement with siblings, or developmental disability (Barth et al, 1988;Barth & Miller, 2000;Groze, 1996;Haugaard et al, 1999;Henry, 1999;Smith et al, 1998). Also, previous research has indicated that service factors may increase the risk of discontinuity, including a low or inadequate level of pre-or post-permanency support or training for adoptive or guardianship caregivers (Barth & Miller, 2000;Rosenthal, Groze, & Aguilar, 1991;Testa, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation